Tricuspid valve repair with Dacron band versus DeVega or segmental annuloplasty. Hospital outcome and short term results - Abdelgawad, Ahmed (Egypt Heart J, 2017)
BACKGROUND: The purpose of this study was to compare the hospital outcome and short term results of tricuspid valve (TV) repair with three repair techniques for functional tricuspid regurgitation (TR), namely, flexible Dacron band, DeVega and segmental annuloplasty. METHODS: A total of 60 patients underwent TV repair at National Heart Institute from January 2013 to November 2014, of which 20 had DeVega procedure (DV), 20 had a segmental annuloplasty (SA) procedure and 20 had a Dacron band (DB) procedure. Concomitant procedures done for rheumatic left sided valve pathology consisted of mitral valve replacement in 70% of patients, and double valve replacement in 30% of patients. Clinical and echocardiographic follow-up data were obtained. Follow-up was 100% complete and was concluded after one year. RESULTS: All demographic criteria and preoperative characteristics of the three studied groups were comparable except for preoperative right ventricular (RVEDD) size that was significantly bigger in Dacron band group as compared to the other two groups (3.18 ± 0.43 cm compared to 3.00 ± 0.33 cm (DV) and to 2.88 ± 0.35 cm (SA), p value of (0.045)). Similarly, all operative and postoperative criteria were comparable among the study groups. Noticeably, (RVEDD) size remodeled better postoperatively in (DB) group as compared to the other two groups, (2.54 ± 0.26 cm compared to 2.83 ± 0.311 cm (DV) and to 2.72 ± 0.29 cm (SA), mean difference values were group (0.64 ± 0.47 cm) for (DB) compared to (0.18 ± 0.29 cm) for (DV) or to (0.16 ± 0.45 cm) for (SA) with p value of 0.000. The majority of patients in each group did not have tricuspid regurgitation (TR) or mild degree (+1) of (TR) on discharge. After one year of follow-up, most of the patient had either no regurgitation or grade (+1 TR). Two patients (10%) in DV group and one patient (5%) in SA group had (+3 TR). There was no statistical significance in the incidence of hospital mortality, only one patient died in DB and one in DV group (5%) and no death happened after hospital mortality for the three groups after one year. CONCLUSIONS: The three techniques are options to repair the tricuspid valve, however, placement of Dacron band in patients undergoing tricuspid valve repair is associated with better RV remodelling, and hence, a probable better right ventricular performance and better outcome of repair is expected. A higher number of patients are needed with longer follow up period to appreciate the effect on survival and rate of freedom from tricuspid regurgitation and re-intervention.